2018
DOI: 10.15294/jdm.v9i2.16417
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors that Influence Dividend Payout Ratio of Coal Companies in Indonesia Stock Exchange

Abstract: The purpose of this study is to analyze the company' s internal and macroeconomic conditions on the ratio of dividend distribution, as well as knowing the conditions of coal companies on the IDX during the decline in coal prices. The weakening of the global economy has resulted in a decline in various commodity prices, including coal prices. Various studies were conducted to determine the factors that influence the poor condition of sectoral mining indices in these weakening conditions a few years ago. The coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
4
9
1
3
Order By: Relevance
“…In which dividend payments increase when the price of oil is low. This study contradicts previous research, namely Sim and Zhou (2015), Raza et al (2016) Kusuma et al (2018 which found positive results. This is due to previous research on the subject of mining.…”
Section: Analysis and Explanationcontrasting
confidence: 99%
See 1 more Smart Citation
“…In which dividend payments increase when the price of oil is low. This study contradicts previous research, namely Sim and Zhou (2015), Raza et al (2016) Kusuma et al (2018 which found positive results. This is due to previous research on the subject of mining.…”
Section: Analysis and Explanationcontrasting
confidence: 99%
“…Because the company will pay more interest than its profits. However, this study is in line with the results of Moon et al (2015) and Kusuma et al (2018) who found that debt policy has no effect on dividend policy. This is possible because companies with high debt ratios will get profits in the following year, while the current profits will be allocated to pay debt contracts that may be due.…”
Section: Analysis and Explanationsupporting
confidence: 92%
“…Posisi dari nilai ROA yang tinggi menunjukkan bahwa perusahaan berkemampuan dalam menghasilkan keuntungan yang berbanding dengan aset yang relatif tinggi (Atmoko et al, 2018). Penelitian Kusuma et al (2018), (Hanif & Bustaman, 2017)) serta (Sumampow & Murni, 2016) menyatakan bahwa ROA berpengaruh positif terhadap dividend payout ratio. Sebaliknya Demirgüneş & Üniversitesi (2015) dan Atmoko et al (2018) menyatakan bahwa ROA berpengaruh negatif terhadap DPR.…”
Section: Abstrakunclassified
“…Penelitian yang dilakukan oleh Nugroho & Sinabutar (2015), Herawati & Fauzia (2018), dan Nerviana (2015), Malik et al (2013) membuktikan hasil signifikan negatif. Sedangkan Fitri et al (2016), Kusuma, Hartoyo, & Sasongko (2018), dan Al-khadiri & Alzomaia (2013) tidak mendapatkan hubungan signifikan. H4: Solvabilitas berpengaruh negatif terhadap dividend payout.…”
Section: Solvabilitas Dan Dividend Payoutunclassified
“…Hasil uji variabel solvabilitas pada penelitian ini sejalan dengan penelitian yang dilakukan oleh Nugroho dan Sinabutar (2015), Herawati dan Fauzia (2018), Nerviana (2015), dan Malik et al (2013). Akan tetapi berbeda dengan penelitian yang dihasilkan oleh Fitri et al (2016), Kusuma et al (2018), Al-khadhiri dan Alzomaia (2013) yang tidak mendapatkan hubungan signifikan.…”
Section: Pengaruh Solvabilitas Terhadap Dividend Payoutunclassified